Architectural graphic standards - Hedges, Keith E.; American Institute of Architects (2016)
A reference for building design and construction professionals. The twelfth edition features: up-to-date codes and standards, with over 300 new drawings, tables, and diagrams; new coverage of building resiliency, emphasizing the building envelope; material properties and performance analyses, with expanded materials selection; environmental factors including climate, thermal comfort, daylighting, and acoustics; sustainability and Universal Design principles integrated throughout the text.
Section 1. Design principles & construction documentation : Functional planning : Human factors ; Universal and accessible design -- Environment : Environmental factors ; Solar path and solar angle ; Climate zone ; Thermal control ; Daylighting ; Acoustics -- Building resiliency : Overview ; Components of building resilience ; Hazard-specific building-resilience considerations ; Maintainability ; Safety ; Security ; Security planning and design: continuing education ; Sustainability ; Good practices in resilience-based architectural designs ; Crime prevention through environmental design ; Lifecycle considerations in resilience-based design -- Architectural construction documentation : Drawings ; Construction specifications ; Building Information Modeling (BIM) ; Procurement documents -- Section 2. Materials : Concrete : Concrete forming and accessories ; Concrete reinforcing ; Typical components applicable to concrete work -- Masonry : Typical components applicable to masonry work ; Glass unit masonry ; Stone assemblies ; Masonry mortaring and grouting ; Masonry anchorage, reinforcing, and accessories ; Installation guidelines and construction tolerances -- Metals : Common characteristics, standards and practices ; Typical metal products incorporated into applicable work results ; Decorative metal ; Installation guidelines and construction tolerances -- Wood, plastics, and composites : Common characteristics, standards, and practices ; Wood classification ; Wood treatment ; Typical wood, plastic, and composite products incorporated into applicable work results ; Installation guidelines and construction tolerances -- Glass : Common characteristics, standards, and practices -- Section 3. Building elements : Element A: Substructure : Soils and soils explorations ; Foundations ; Cast-in-place concrete slab ; Crawl space construction ; Basement construction -- Element B: Shell : Design considerations ; Sustainability and energy ; Floor assemblies ; Roof assemblies ; Superstructure ; Exterior vertical enclosures ; Exterior horizontal enclosures -- Element C: Interiors : Interior construction -- Element D: Services : Conveying ; Other conveying equipment ; Plumbing ; Heating, ventilating, and air-conditioning (HVAC) : Design considerations ; Heating/cooling source components ; HVAC distribution arrangements and components ; HVAC delivery components ; HVAC control systems ; Fire protection ; Electrical ; Communications -- Element E: Equipment and furnishings : Equipment ; Furnishings -- Element F: Special construction : Design considerations of integrated construction ; Building modules ; Manufactured: fabricated rooms ; Special structures ; Manufactured engineered structures ; Special function construction ; Special facilities components ; Athletic and recreation special construction -- Element G: Sitework : Site earthwork ; Runoff control systems ; Water management ; Basement excavation ; Site grading ; Site improvements ; Parking lots ; Porous pavement ; Pedestrian paving ; Exterior stairs and ramps ; Athletic and recreation areas ; Site development ; Landscaping ; Selecting plants for rooftop planting ; Site civil utilities ; Porous paving systems ; Storm drainage grates ; Manholes, inlets, and catch basins ; Site electrical utilities -- Appendices : Classical architectural elements -- Mathematical data -- Structural calculations.
Includes bibliographical references and index.
Keywords: Building -- Details -- Drawings -- Standards; Architectural drawing -- Standards; Standards, Engineering; Architectural drawing -- Standards; Building -- Details -- Drawings -- Standards; Standards, Engineering; Arkitekturritningar; Byggnadsteknik